The Adaptation of Medical Records to Epidemiological Use - Jeanty, Cl (Methods of Information in Medicine, 1965)
A method is described in an attempt to make medical records suitable for epidemiologigri: purposes. Every case of a disease is recorded on an appropriate punched card with the object of working towards a general description of a disease through the collation of several cases of the same diagnosis. This punched card represents a very great condensation of the original record. Special care has been applied to state as precisely as possible the time variable, particularly as far as its origin and unit of measure are concerned, in order to demonstrate the existence of causal relations between diseases. Such cards are also intended to make easier statistical studies in clinical pathology, in evaluation of new laboratory techniques, and in therapeutical trials.